The role of Banate Bay Resource Management Council, Inc. in the promotion of social capital of fisher folks of Banate, Iloilo, Philippines - Fara-on, Aubry F.
One of the integrated approaches on community Based Coastal Resource Management (CBCRM) is the co-management approach, which initiates collaborative interactions among different sectors to properly manage coastal resources. This enabled the sharing of resources, visions and expertise to achieve sustainanble development and to empower the people in the community. Such was the case in the creation of Banate Bay Resource Management Council, Inc. (BBRMCI) in the Barotac and Banate Bay. BBRMCI was the first LGU-initiated community resource management program in Iloilo, which is comprised of the municipalities of Anilao, Banate, Barotac Nuevo and Barotac Viejo. The BBRMCI has played a pivotal role in the promotion of coastal prreservation through the collaborative efforts between the local governments concerned., This study aimed to (1)determine the degree of understanding, usage and promotion of social capital of the BBRMCI, (2)determine and analyze the level of horizontal social capital operating before and during the operation of BBRMCI as evaluated by the fisher folks of Banate, (3)determine and analyze the level of vertical social capital operating before and during the operation of BBRMCI as self-evaluated by the fisher folks of Banate, and (4)evaluate the effects of social capital development promoted by the BBRMCI on the lives of the fisher folks of Banate. The methods applied to answer objectives of the study include secondary-data analysis, key informant interview and structured interview (open and close-ended questions and statements). The structured interview was design to elicit fisher folks perceptions on the levels of their social capital and the benefits they acquired. The questionnaire is composed of statements in the form of a Likert Scale and questions to measure the level of social capital of fisher folks before and during the operation of BBRMCI. The respondents of the study are members of the Barangay Fisheries and Aquatic Resource Management Councils of Banate which are also registered members of BBRMCI. They were made to answer the structuredsurvey questionnaire individually. The Executive Director of BBRMCI was chosen as the key informant of this study. The study observed that the BBRMCI is promoting social capital implicitly and unconsciously through its programs and projects. Respondents also perceived that although Banate Bay is properly managed by the BBRMCI, still a majority perceived that their lives are much better before the operation of BBRMCI. Results also showed that the level of horizontal and vertical social capital of the fisher folks increased during the operation of BBRMCI and a majority of the respondents have acquired benefits from the programs and projects of the BBRMCI. Apparently, less than half of the total respondents believed that their lives improved because of the benefits acquired from BBRMCI.